2015
DOI: 10.1024/1422-4917/a000331
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior in German Adolescents

Abstract: Suicidal behavior was reported more often when adolescents demonstrate symptoms of mania as well as symptoms of depression than when they demonstrate only depressive symptoms. The presence of bipolar symptoms in adolescents should alert clinicians to the heightened possibility of suicidal behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Previous studies indicated that the high risk of suicide among AWD increased caregivers' supervision of AWD and in turn decreased caregivers' emotional well-being and increased their stress. 44,45 Moreover, the negative emotion was also associated with poorer mental QoL among caregivers of AWD, which were supportive of the findings of the qualitative data in this study. The caregivers often felt guilt about their child's illness and were concerned about their future, which resulted in their feeling overwhelmed by care-giving.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies indicated that the high risk of suicide among AWD increased caregivers' supervision of AWD and in turn decreased caregivers' emotional well-being and increased their stress. 44,45 Moreover, the negative emotion was also associated with poorer mental QoL among caregivers of AWD, which were supportive of the findings of the qualitative data in this study. The caregivers often felt guilt about their child's illness and were concerned about their future, which resulted in their feeling overwhelmed by care-giving.…”
Section: Discussionsupporting
confidence: 88%